Penyuluhan dan Pelatihan Pembuatan Minuman Jahe Merah untuk Pemanfaatan Tanaman Obat Keluarga di Desa Linggasari - Royani, Sri; Yunarti, Kresensia Stasiana; Majid, Sinta Fadhilah (UNIB Press, 2024)
Red ginger is a type of ginger found in Indonesia. Apart from being widely used as a kitchen spice, red ginger contains essential oils which can be used as medicine. The active substances in essential oils have properties for preventing and treating various diseases, such as coughs, dizziness, aches, angina and nausea. Linggasari Village is one of the villages in Kembaran District, Banyumas Regency which is currently still developing. Through the observation process, it was discovered that the residents of this village had planted a lot of red ginger plants, but they had not yet utilized them optimally for health. Therefore, counseling and training on making red ginger drinks was carried out in this village. This was done as an effort to use red ginger as a family medicinal plant in the village. The residents of Linggasari Village were very enthusiastic about participating in this activity. After providing counseling and training, it is hoped that the villagers will be able to use red ginger as a medicinal drink that they can make themselves and is beneficial for their health.